New Strategy for Microbial Corrosion Protection: Photocatalytic Antimicrobial Quantum Dots - Shijia Liu; Dapeng Wu; Jie Zheng; Baochen Han; Jian Qi; Fanchun Meng; Jianhui Li; Dan Liu (Nanomaterials)
Microbial corrosion has significant implications for the economy, environment, and human safety worldwide. Photocatalytic antibacterial technology, owing to its advantages in environmental protection, broad-spectrum, and efficient sterilization, presents a compelling alternative to traditional antibacterial strategies for microbial corrosion protection. In recent years, photocatalytic quantum dot materials have garnered considerable attention in this field due to their unique quantum effects. This article provides a brief overview of the quantum effects associated with quantum dot materials, reviews the classification and preparation methods of these photocatalytic quantum dots, and elucidates their inhibitory effects and mechanisms against microbial corrosion. Finally, this article summarizes unresolved issues and prospects for the future development of quantum dots in the realm of microbial corrosion protection.